Pathological Elements in Analog Circuit Design (Lecture Notes in Electrical Engineering,, 2018)
This book is a compilation and a collection of tutorials and recent advances in the use of nullors (combinations of nullators and norators) and pathological mirrors in analog circuit and system design. It highlights the basic theory, trends and challenges in the field, making it an excellent reference resource for researchers and designers working in the synthesis, analysis, and design of analog integrated circuits. With its tutorial character, it can also be used for teaching. Singular elements such as nullors and pathological mirrors can arguably be considered as universal blocks since they can represent all existing analog building blocks, and they allow complex integrated circuits to be designed simply and effectively. These pathological elements are now used in a wide range of applications in modern circuit/system theory, and also in design practice.